IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE DALAM MENINGKATKAN KUALITAS PELAYANAN ORGANISASI KEMASYARAKATAN (ORMAS) PADA BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
Implementation of the principles of good governance with the aim of creating good governance, one of which is through accountable public services. The implementation of good governance is an absolute necessity for the majority of the people in order to create a political system of government that is in favor of the interests of the people. The implementation of good governance is an urgency in an effort to realize an effective and efficient regional government that is independent and free from corruption, collusion and nepotism. The purpose of this study is to find out the Implementation of Good Governance Principles in Improving the Quality of Community Organization Services (ORMAS) in the National Unity and Politics Agency of Tabalong Regency. The method used in this research is a qualitative descriptive approach. This research was obtained by field observations, interviews and documentation. The data analysis technique used in this study is the data analysis interactive model of Miles and Huberman. There were 5 (five) informants in this study, including the Head of the Kesbangpol Agency for Tabalong Regency, the Head of Politics and Community Organizations, and the Community. The results of the research on the Implementation of the Principles of Good Governance in Improving the Quality of Service for Community Organizations (Ormas) at the National Unity and Political Agency of Tabalong Regency are categorized as highly implemented. Based on the results of the research conducted, it can be concluded that the Implementation of Good Governance Principles in Improving the Service Quality of Community Organizations (Ormas) at the National Unity and Political Agency of Tabalong Regency is categorized as